Integrasi Nilai Islam dalam BK The Integration of Islamic Values in Guidance and Counseling Services for Enhancing Student Character: A Thematic Interpretation Study of Educational Verses in the Quran as a Literature Review - Hexa Putri, Sri Maizurrahmi; Zaini, Hasan; Irman, Irman (The Future of Education Journal, 2026)
This literature study using a thematic interpretation approach was conducted to examine how Islamic values are integrated into guidance and counseling services to strengthen students’ character. The findings reveal that the value of tauhid (Islamic monotheism) serves as the foundation for fostering integrity and social awareness, which are essential for counselors in professional practice. The provision of counseling services incorporating spiritual elements has proven effective in shaping students’ character. It is expected that guidance and counseling teachers consistently apply this approach and develop Islamic-integrated counseling service modules in order to optimize the implementation of counseling services.